Impact of Business Process Digitalization, Work Flexibility, and Family Support on Employee Performance (Case Study in West Sumatra and the Riau Islands) - Br Ginting , Emmi; Harsasi, Meirani; Khurniawan, Arie Wibowo; Yusriani, Sri (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Abstract: This study aims to analyze the impact of business process digitalization, work flexibility, and family support on employee performance, with work-life balance as an intervening variable at the Regional Office of the Directorate General of State Assets (DJKN) in Riau, West Sumatra, and the Riau Islands. The research employs a quantitative causal method and descriptive statistical analysis. Data were collected through a questionnaire distributed to 177 respondents, who are civil servants within the DJKN Regional Office in the specified regions. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that business process digitalization has a positive and significant direct effect on performance and work-life balance, but it does not significantly influence performance through work-life balance as an intervening variable. Work flexibility positively and significantly affects performance directly, as well as work-life balance, and also has a significant positive impact on performance through work-life balance. Family support has a positive and significant direct effect on performance and work-life balance, but it does not significantly influence performance through work-life balance as an intervening variable. Keywords: Business Process Digitalization, Work Flexibility, Family Support, Work-Life Balance, Employee Performance